ANALISIS KEMAMPUAN COMPUTATIONAL THINKING MAHASISWA CALON GURU MATEMATIKA PADA PROGRAM PROFESI PENDIDIKAN GURU - anggi anatasia kinanti; Syahlan Syahlan; Rosliana Siregar (MES: Journal of Mathematics Education and Science, 2025)
This study aims to analyze the Computational Thinking (CT) abilities of prospective mathematics teacher students enrolled in the Teacher Professional Education Program at Universitas Islam Sumatera Utara. Using a descriptive quantitative approach, CT abilities were examined based on four main indicators: decomposition, pattern recognition, abstraction, and algorithmic thinking. Data were collected through contextual open-ended tests, perception questionnaires, and limited interviews involving 24 PPG students. The results showed that, in general, students' CT abilities fell into the moderate category, with the highest achievement in pattern recognition and the lowest in abstraction. Most students had never received explicit instruction in CT, yet acknowledged that this approach helped them solve mathematical problems more systematically. These findings highlight the importance of explicitly integrating CT skills into mathematics education curricula through problem-based and digital literacy-oriented learning approaches. The study recommends strengthening instructional strategies to develop students’ systematic and logical thinking abilities as future mathematics educators.